A Mixed Methods Cross‐Cultural Study to Compare Youth Drinking Cultures in Italy and the USA. Issue 1 (1st September 2019) - Aresi, Giovanni; Cleveland, Michael J.; Vieno, Alessio; Beccaria, Franca; Turrisi, Robert; Marta, Elena
Abstract : Aims: To compare the drinking cultures of youth in the USA and in Italy. Method: Sequential explanatory mixed method design. Phase 1: Multigroup latent class analysis was used to identify subgroups of drinkers from samples of 424 (61.3% female) Italian and 323 American college students (57.3% female). Phase 2: Focus group interviews with 41 Italian and 47 American youth were used to collect narratives on features of the two drinking cultures. Results: Four partially invariant subgroups of drinkers were found. Most participants (>75%) in both countries concentrated drinking during weekends. Overall, US drinkers displayed greater probabilities to report risky drinking behaviors and experience negative consequences as compared to comparable subgroups of Italian drinkers. Discrepancies in terms of socialisation processes during childhood (i.e. permissiveness) and underlying cultural assumptions with regard to alcohol consumption (i.e. purposes of alcohol use) may explain differences in how alcohol is used in the two countries. Conclusions: Findings suggest that there are crucial differences in societal schema of beliefs, informal social norms, practices, and values attached to alcoholic beverages across the USA and Italy. These results demonstrate the need for culturally tailored alcohol preventive interventions and clinical practice targeted to young people that capitalise on such differences.